Roles of Alloying Elements on the Passivity of W-xCr-yNi Alloys in Aggressive Environments - Kharel, PL; Sah, SP; Bhattarai, J (Nepal Journal of Science and Technology, 2014)
The role of alloying elements on the passivity of the sputter−deposited amorphous or nanocrystalline W-xCr-yNi alloys in 12 M HCl, 0.5 M NaCl and 1 M NaOH solutions open to air at 30°C was studied by corrosion tests and electrochemical measurements. All the examined sputter-deposited W-(42-75)Cr-(4-15)Ni alloys, which are composed of either amorphous or nanocrystalline single phase solid solution, showed higher corrosion resistance than those of alloying elements (i.e. tungsten, chromium and nickel) in 12 M HCl, 0.5 M NaCl and 1 M NaOH solutions. All the alloys used in this study showed higher corrosion resistance than those of the alloying elements in the aggressive environments. Anodic current densities of the alloys decreased with increasing chromium contents and became lower than that of chromium. Transpassive dissolution of chromium was significantly enhanced by the simultaneous additions of tungsten, chromium and nickel in aggressive environments of 12 M HCl, 0.5 M NaCl and 1 M NaOH. Hence the synergistic effect of chromium addition in enhancing the corrosion resistance of the W-xCr-yNi alloys was clearly observed from the present study. DOI: http://dx.doi.org/10.3126/njst.v14i2.10418 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 65-72